2004
DOI: 10.1111/j.1601-5223.2001.t01-1-00171.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Intergenomic Translocations Involving Wheat, Hordeum Vulgare and Hordeum Chilense Chromosomes by FISH

Abstract: Interspecific and intergeneric hybrids in the Triticeae are valuable for transfers of genes from one species to another and to extend the range of genetic variation available to plant breeders. For a long time, one goal of cereal breeders has been the production of amphiploids between wheat and barley in order to combine desirable features from both species. Since the first success achieved by KRUSE (1973) crossing cultivated barley and wheat (Hordeum vulgure x Triticum aestivum, T. turgidum, and T, monococcum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 17 publications
0
31
0
Order By: Relevance
“…The use of total genomic DNA as species-specific probes resulted in an efficient procedure to distinguish between different genomes in the material analysed. FISH, including the multi-colour combinations, has been successfully used for wheat and its relatives Prieto et al, 2001). In this study, the quality of hybridization was highly satisfactory and clearly differentiated between wheat, H. vulgare and H. chilense genomes without the use of blocking DNA.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…The use of total genomic DNA as species-specific probes resulted in an efficient procedure to distinguish between different genomes in the material analysed. FISH, including the multi-colour combinations, has been successfully used for wheat and its relatives Prieto et al, 2001). In this study, the quality of hybridization was highly satisfactory and clearly differentiated between wheat, H. vulgare and H. chilense genomes without the use of blocking DNA.…”
Section: Resultsmentioning
confidence: 92%
“…Genomic in situ hybridisation (GISH) and fluorescent in situ hybridisation (FISH) are well-established and highly efficient techniques for chromosome identification. In situ hybridisation readily distinguishes H. chilense and H. vulgare chromosomes from those of wheat Prieto et al, 2001) and permits the assessment of the physical size of introgressed segments.…”
Section: Introductionmentioning
confidence: 99%
“…The remaining translocation with no transgene integration was a Robertsonian translocation (Barro et al, 2003 (Fig. 2g) were most frequent, followed by wheat-H. chilense and wheat-H. vulgare intergeneric translocations (Prieto et al, 2001). These lines may be useful for introgressing characters of interest from H. vulgare into tritordeum.…”
Section: Chromosome Translocations Involving H Chilense Barley or Wmentioning
confidence: 99%
“…The use of molecular markers combined with in situ hybridisation is very useful for finding exogenous genetic introgressions (Schwarzacher et al 1989; Calderón et al 2012; Zhao et al 2013), but the exogenous chromosome fragment needs to be previously identified and well characterised in order to choose specific molecular markers that will allow the alien sequence to be unequivocally distinguished from the equivalent chromosome region in wheat, which can sometimes be difficult. In addition, in situ hybridisation enables the determination of the exact chromosomal compositions in the descendence of genetic crosses between wheat and related species (Prieto et al 2001). However, although in situ hybridisation is an enormously informative genetic approach, it requires high expertise and is time consuming, making the cytogenetic approach expensive when there is a need to analyse hundreds of plants resulting from genetic crosses.…”
Section: Introductionmentioning
confidence: 99%